EFEKTIVITAS PENDEKATAN PEMBELAJARAN PROBLEM POSING TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Syahriani Syamsuddin; Thamrin Tayeb; Muhammad Rusydi Rasyid; Andi Ika Prasasti Abrar; Badaruddin Amin (Al Asma: Journal of Islamic Education, 2022)
Problem posing is a problem-posing-based learning approach to train students' reasoning power and critical thinking skills. This study aims to determine whether the use of a problem posing learning approach is effective in improving mathematics learning outcomes. in class XI IPA SMA Negeri 11 Makassar. students of class XI IPA SMA Negeri 11 Makassar. This research is a quasi-experimental research design using a nonequivalent control group design. The population in this study were all students of class XI IPA SMA Negeri 11 Makassar consisting of 165 students while the samples were students of class XI IPA2 as the experimental class and students of class XI IPA3 as the control class, each consisting of 33 students. The instrument used in this study was a test of student learning outcomes, in the form of pretest and posttest. The analytical technique used is descriptive statistical analysis and inferential statistical analysis. The research results show that the problem posing learning approach is effective in improving the mathematics learning outcomes of class XI science students. SMA Negeri 11 Makassar.